Design and Numerical Analysis of a Micro Gas Turbine Combustion Chamber - Mangra, A. C. (Engineering, Technology & Applied Science Research, 2020)
The interest in micro gas turbines has been steadily increasing. As a result, attention has been focused on obtaining optimal configurations for micro gas turbines depending on the applications in which they are used. This paper presents the CFD modeling results regarding an annular type combustion chamber, part of an 800N micro gas turbine, predestined to equip a small scale multifunctional airplane. Two configurations have been taken into consideration and 3D RANS numerical simulations have been conducted with the use of the commercial software ANSYS CFX. The liquid fuel droplets were modeled by the particle transport model, which tracks the particles in a Lagrangian way. An initial fuel droplet diameter of 500µm has been imposed. The numerical results obtained are encouraging. The flame was developed in the central area of the fire tube, its walls thus not being subjected to high temperatures. Also, the maximum temperatures were obtained in the primary zone of the fire tube. The temperature then decreased in the fire tube’s secondary zone and dilution zone. The numerical results will be validated by conducting combustion tests on a testing rig which will be developed inside the institute’s Combustion Chamber Laboratory.